The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1023/a:1009209408034
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Autopsied liver tissue samples collected from 42 males and 31 females were analyzed for copper, manganese and zinc using atomic absorption spectrometry (AAS). With the exception of two liver samples for which the copper levels were determined to be 74.8 and 104.0 micrograms/g (dry weight), hepatic copper concentrations were found to range from 1.7 to 32.4 micrograms/g with a mean concentration of 14.2 micrograms/g and standard deviation of 7.0 micrograms/g. Manganese concentrations (with the exception of one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Increased content of Cu 2+ in the brain can be associated with the formation and realization of the functions of the brain nervous system. Using AAS, it was shown that the average content of Cu in human liver is 14.2 ± 7.0 μ g/g (dry weight) [54], which agree with our data 19.8 ± 5.7 μ g/g (Table 2). The content of copper in organs of the Russian and Japanese samples [46] is in good agreement (Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Increased content of Cu 2+ in the brain can be associated with the formation and realization of the functions of the brain nervous system. Using AAS, it was shown that the average content of Cu in human liver is 14.2 ± 7.0 μ g/g (dry weight) [54], which agree with our data 19.8 ± 5.7 μ g/g (Table 2). The content of copper in organs of the Russian and Japanese samples [46] is in good agreement (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…Taking into account the range of the values, the average Zn content in our group was significantly higher than that of the Japanese group [46] only in the case of lungs (208 ± 35 and 62 ± 19 μ g/g). Zn content in the liver ranged from 38.5 to 231.3 μ g/g, and the average value was 118.3 ± 44.4 μ g/g [54]. The zinc content in the liver of the donors studied by us was noticeably higher: range 140–520 μ g/g and average value 272 ± 153 μ g/g (Supplementary ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The RCT was rated as good quality, the case-control study was rated as poor quality, and the cross-sectional studies were generally of reasonable quality (see Appendix S3 in the Supporting Information online ). Tissue samples comprised bone (n = 4) (ie, rib, vertebrae, femur), 29 , 111 , 116 , 118 muscle (n = 4) (ie, diaphragm, abdominal wall, and gluteal area), 27 , 28 , 30 , 43 organs (n = 23) (ie, aorta, brain, eye, glands, gastrointestinal tract, heart, kidney, liver, lung, and skin), 28 , 40–46 , 108–115 , 117 , 119–122 and whole blood (n = 1). 71 Details of these studies are provided in Table S4 in the Supporting Information online , and the forest plot, including data from all ages, is presented in Figure S9 in the Supporting Information online .…”
Section: Resultsmentioning
confidence: 99%